Verbal Number in Tagom: Rashad Group - Aldawi, Maha A. (AAeO - Afrikanistik-Aegyptologie-Online, 2022)
The current study is anattempt to shed light on verbal number in Tagom one of the derivational processes in the verbal morphology of the language. Tagom is one of the four varieties of Tegali of the Rashad group which itself belongs to the Niger-Congo phylum (Greenberg 1963, Schadeberg 1981, Williamson& Blench 2000, Quint 2009, Blench 2013, Dimmendaal 2018). The objective of this study is to investigate verbal numberand specifically pluractional marking in Tagom. Verbal number isa grammatical device that indicates that the actionstransmitted by a verb are repeated or that multiple participants performing certain actions are involved (cf. Creisselset al.2007, Veselinova  2013). The  notion  of  verbal  pluractional marking  is  restricted  to  “plurality  or multiplicity of the verb’s action” which was first introduced by Paul Newman (1990:53-54) in his survey of this phenomenon in Chadic languages. The study focuseson answering the following: When does verbal number, i.e., participant number and/or event number, surface in Tagom? What are the different strategies used in Tagom to indicate pluractionality? What is the correlation between transitivityand verbal numberin Tagom? What are the semantic connotations of verbal number in Tagom?